2013
DOI: 10.1293/tox.26.283
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Edema Due to Oral Gavage in a Toxicological Study Related to Aquaporin-1, -4 and -5 Expression

Abstract: A one-time oral gavage can be enough to cause of alveologenic edema with higher expression of AQP-1 and -4 than that with repeated-dose oral gavage, which caused both profound perivascular edema and hydrostatic pressure edema, while AQP-5 was similarly expressed. The alteration of AQPs expression was probably related to alveolar fluid clearance across the alveolar and bronchiolar epithelium in different stages of lung injury. The results clarified the type of lung edema in acute and sub-chronic toxicity studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Studies by the Verkman group, employing genetic knock-down of aquaporins, revealed a minor contribution of the transcellular, and therefore TJ independent pathway, on transepithelial water transport in the lung [83, 84, 114, 130, 131], suggesting a major contribution of TJ-dependent paracellular water flux to overall transepithelial water flux. However, other studies found that perturbations of aquaporin activity disturb transepithelial water transport and volume homeostasis in the airways [2, 32, 35, 113, 127], suggesting that TJ-independent water transport pathways through aquaporins contribute significantly to fluid transport across the airway epithelium. A more recent study now suggests that both processes occur in a different manner, where basal water transport activity is dominated by a paracellular pathway, whereas a compensatively increased water resorption is predominantly carried by an aquaporin-dependent transcellular pathway [110].…”
Section: Caludins Of the Alveolar And Airway Epitheliummentioning
confidence: 99%
“…Studies by the Verkman group, employing genetic knock-down of aquaporins, revealed a minor contribution of the transcellular, and therefore TJ independent pathway, on transepithelial water transport in the lung [83, 84, 114, 130, 131], suggesting a major contribution of TJ-dependent paracellular water flux to overall transepithelial water flux. However, other studies found that perturbations of aquaporin activity disturb transepithelial water transport and volume homeostasis in the airways [2, 32, 35, 113, 127], suggesting that TJ-independent water transport pathways through aquaporins contribute significantly to fluid transport across the airway epithelium. A more recent study now suggests that both processes occur in a different manner, where basal water transport activity is dominated by a paracellular pathway, whereas a compensatively increased water resorption is predominantly carried by an aquaporin-dependent transcellular pathway [110].…”
Section: Caludins Of the Alveolar And Airway Epitheliummentioning
confidence: 99%
“…However, regarding gavage-related reflux and technical gavage errors, it is now considered that even very small amounts of the treated material, 20 µl, are able to induce serious irritation in the respiratory tract and mortality. Mechanically induced reflux is considered as the most likely cause of reflux in rats (23). In both compared protocols, 20 mg/kg body weight of 2-AAF was given to animals by gavage in a final volume of 0.5 mL; therefore, this volume was enough to induce respiratory alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is necessary to analyze the FAH phenotype evolution through time in our experimental models. Third, to avoid respiratory complications due to gavage, the amount of toxic agent administrated and the irritancy and the viscosity of the test formulations, among others considerations, should be controlled (23).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological characteristics of lung edema include fluid accumulation in the alveolar and interstitial lung. Many research studies have shown that AQP is involved in the pathogenesis of lung edema (Singha et al, 2013). At present, 13 types of AQPs have been found in mammals (AQP 0-12), 6 of which are distributed in the lung tissues (AQP-1, -3, -4, -5, -8, and -9) (Zhu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%